The relationship between satisfaction level and products bought online in a post-pandemic context the case of Lazada, Shopee, and Tiktok Shop - Carrera, Gabriel Ripalda; Esperas, Frances Mae Calucer; Lacaba, Mikaela Ong; Roldan, Kharyza Mae Bulanadi; Lorenzo, Anida Bernadette (Tacloban City Division of Management, University of the Philippines Tacloban College, 2025)
The surge in e-commerce during the COVID-19 pandemic has reshaped consumer purchasing behaviors, with platforms like Lazada, Shopee, and TikTok Shop becoming dominant marketplaces in the Philippines. Even as restrictions eased, online shopping continued to grow, driven by convenience and accessibility. However, rising consumer concerns regarding product quality, pricing, and fulfillment reliability highlight the importance of evaluating customer satisfaction across different product categories This study examined the relationship between satisfaction levels and product categories purchased on these platforms, identifying significant variations across Fashion, Beauty and Personal Care, Food and Beverage, Consumer Electronics, and Furniture and Home Appliances. Through web scraping and statistical analysis of 15,000 product ratings, findings revealed that Food and Beverage and Beauty and Personal Care consistently achieve the highest satisfaction, while Consumer Electronics and Furniture and Home Appliances demonstrated areas that require improvement. Results from Kruskal-Wallis test and Chi-Square tests confirmed that platform choice significantly influences satisfaction levels, emphasizing the need for targeted improvements in lower-performing categories. These insights contribute to evidence-based recommendations for sellers and platform operators, enhancing customer experience and fostering sustainable e-commerce growth in the Philippines.
Undergraduate thesis (Bachelor of Science in Accountancy) -- University of the Philippines, Tacloban.
Keywords: Electronic commerce; E-commerse platforms; Customer satisfaction; Product categories; Lazada; Shopee; TikTok shop; Web scraping